2017
DOI: 10.1007/s11239-017-1497-x
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive warfarin dose reduction after initiation of sulfamethoxazole-trimethoprim or metronidazole

Abstract: To evaluate the utility of a preemptive warfarin dose reduction at the time of initiation of either sulfamethoxazole-trimethoprim or metronidazole, a retrospective chart review of patients who received an outpatient prescription for warfarin and either sulfamethoxazole-trimethoprim and/or metronidazole from July 1, 2011 to July 1, 2015 was conducted. Clinical outcomes compared Veterans who had a warfarin dose reduction and those who did not within 120 h (5 days) of antibiotic initiation. The primary outcome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…37 It was therefore expected that the concomitant use of metronidazole and warfarin notably increased the INR levels in our study, although to a lesser extent than miconazole or amiodarone. Hence, concomitant therapy with metronidazole should be optimized through warfarin dose adjustment, as the results of a recent study suggest; Powers et al 38 found that a pre-emptive mean reduction of 25% in warfarin dose resulted in maintained therapeutic INR levels in the 30 days following metronidazole course and fewer follow-up visits, compared with the group of patients without this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…37 It was therefore expected that the concomitant use of metronidazole and warfarin notably increased the INR levels in our study, although to a lesser extent than miconazole or amiodarone. Hence, concomitant therapy with metronidazole should be optimized through warfarin dose adjustment, as the results of a recent study suggest; Powers et al 38 found that a pre-emptive mean reduction of 25% in warfarin dose resulted in maintained therapeutic INR levels in the 30 days following metronidazole course and fewer follow-up visits, compared with the group of patients without this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These results were more pronounced in patients on metronidazole and sulfamethoxazole-trimethoprim than in patients on levofloxacin. 2325 On the other hand, both RCTs on warfarin–prednisone and warfarin–doxycycline interactions, found more control patients with INR of more than 1 point over the goal upper limit compared to the intervention group but these results did not reach statistical significance. 26,27 There was also a statistical significance increase in the incidence of subtherapeutic INRs in the preemptive group.…”
Section: Discussionmentioning
confidence: 95%
“…Benefit of the use of preemptive warfarin dose adjustment has been studied by others, however, results were conflicting. [23][24][25][26][27] Three of these studies were retrospective observational studies that focused on preemptive dose reduction of warfarin in patients initiating metronidazole, 23,25 sulfamethoxazole-trimethoprim, 23,24 and levofloxacin. 24 While 2 other studies were randomized controlled trials (RCTs) by Dowd and colleagues and they compared preemptive warfarin dose reduction to reactive warfarin dose adjustment in patients receiving prednisone 26 and in patients receiving doxycycline.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reputation of these drugs for causing significant changes in the INR, some clinicians may advocate for empiric warfarin dose adjustments 24,32,[34][35][36] to avoid risk of supratherapeutic or subtherapeutic INR and potentially reduce the number of INR monitoring visits surrounding the drug interaction. Although these drug interactions are fairly common and this may be an effective strategy in some patients, not all patients will respond uniformly, and an empiric dose adjustment in a nonresponder could result in an out-of-range INR.…”
Section: Management Strategiesmentioning
confidence: 99%